Impact of mentorship in the career progression of employees within the financial services industry - Woolnough, David Edward (My University, 2011)
· Organisational sector. Although formal mentoring programmes are the preferred programmes to implement within an organisation, there is value in creating a culture conducive to informal mentoring programmes as these programmes do add value to employee career advancement
MBA - WBS
Keywords: Mentors and mentoring